Biochar amendment and Calamagrostis angustifolia planting affect sources and production pathways of N2O in agricultural ditch systems. Issue 4 (15th March 2019) - Cheng, Qianding; Cheng, Hongguang; Wu, Zhenzhen; Pu, Xiao; Lu, Lu; Wang, Jian; Zhao, Jinbo; Zheng, Aihua
Abstract : Biochar amendment and Calamagrostis angustifolia planting affect N2 O emissions derived from nitrification and denitrification pathways in agricultural ditch systems. Abstract : Nitrous oxide (N2 O) from agricultural ditches is a non-negligible source of anthropogenic greenhouse gas (GHG) emissions, but few studies have addressed this topic in depth. On the other hand, although there are numerous reports that biochar application can affect N2 O emissions from soil, the understanding of the process and source of changes is still incomplete. To examine the effect of biochar and Calamagrostis angustifolia on N2 O emissions, we conducted experiments with constructed ditches where corn stalk biochar (pyrolysis temperature of 450 °C) was applied at a rate of 16.77 Mg ha −1 and C. angustifolia was planted. The sources (native sediment versus exogenous inorganic N) and production pathways (nitrification versus denitrification) of N2 O emissions were discriminated using the 15 N isotope tracer method. We observed that biochar application reduced the cumulative total N-N2 O emissions from the native sediment by 10.8–18.7% and reduced the cumulative 15 N-N2 O emissions from the exogenous 15 N-labelled inorganic N by 25.7–68.6%; C. angustifolia planting reduced these cumulative N2 O emissions by 48.8–53.3% and 93.3–92.4%, respectively. The results showed that biochar stimulated nitrification and nitrification-derived 15 N-N2 O emissions, but reduced denitrification-derived 15 N-N2 O emissions in bare sediment microcosms; C. angustifolia effectively reduced both nitrification-derived and denitrification-derived 15 N-N2 O emissions. Therefore, we concluded that the effect of biochar application on N2 O emissions may depend on its dominant N2 O production pathway and biochar application plus C. angustifolia planting could be beneficial for the mitigation of N2 O emissions in agricultural ditch systems.